The effect of sulphur deficiency and sulphur fertilisation on the nitrogen compounds of timothy - Ettala, Terttu; Kreula, Matti; Tähtinen, Hilkka (Agricultural and Food Science, 1978)
The effect of sulphur deficiency and sulphur fertilisation on the nitrogen compounds of plants was studied, using timothy as the test species. The samples were obtained from 4 field trials performed in northern Finland. The nitrogen and sulphur treatments in each of these trials were as follows: a) N O, S O, b) N 48, S O, c) N 48, S 34, d) N 96, S O and e) N 96, S 68 kg/ha. Nitrogen was applied as NPK compound fertiliser and sulphur in the form of gypsum. In trials 1and 2 sulphur given in addition to nitrogen increased the yield considerably. The contents of soluble-, protein-, a-amino-, ammonium- and nitrate-nitrogen, as well as the free and peptide- and protein-bound amino acids were determined in the harvested timothy. Nitrogen fertilisation did not have any noticeable effect on the protein-nitrogen content of sulphur-deficient plants, but sulphur fertilisation increased it by an average of 26 % (trial 2). The proportion of soluble nitrogen of the total nitrogen in trials 1 and 2 averaged 50 % with N-fertilisation and 37 % with N+S fertilisation. Sulphur fertilisation decreased the contents of a-amino-, ammonium- and nitrate-nitrogen, and also their proportions of the total nitrogen. In those trials (3 and 4) in which sulphur fertilisation did not increase the yield, the proportion of soluble nitrogen of the total nitrogen was an average of 33 % with all treatments. In sulphur-deficient timothy the content of asparagine and aspartic acid totalled 60 % of the content of free amino acids, and their nitrogen formed about 17% of the total plant nitrogen. The corresponding figures with sulphur fertilisation were 39 % and 3.5 %, and in those trials where there was no sulphur deficiency (trials 3 and 4) on average 27 % and 2.5 %, irrespective of fertilisation. The proportion of soluble nitrogen of the total nitrogen of timothy was closely correlated (r = 0.79***) to the N/S ratio, as was the proportion of asparagine plus aspartic acid of the total free amino acids (r = 0.91***). Rikin puutteen ja rikkilannoituksen ...